Preparation of an Instant Drink: Extruded Flour of Polished Red Rice (Oryza Sativa L) and Blackberry (Rubus Spp) Retentate by Microfiltration - Arévalo, Arturo Meléndez; Ascheri, José Luis Ramírez; De Carvalho, Carlos Wanderlei Piler; Freitas, Daniela De Grandi Castro (Discoveries in Agriculture and Food Sciences, 2024)
Red rice (Venetian rice or rice-da-terra) was first introduced to Brazil by Portuguese colonizers in the 17th century. Its cultivation is now limited to small areas in the Northeast, particularly in Paraíba, Rio Grande do Norte, and Pernambuco. This study aimed to develop an easy-to-reconstitute beverage using red rice flour, enhanced with a co-product from blackberry juice clarification through membrane microfiltration (blackberry retentate powder). The red rice flour was processed in a Clextral twin-screw extruder under controlled conditions and dried at 60°C to less than 4% moisture. Using the central composite rotational design and response surface methodology, 13 treatments were tested to optimize physicochemical properties like proximate composition, amino acids, minerals, anthocyanins, and expansion indices (REI, VEI, LEI). Water absorption and solubility indices (WSI, WAI) and paste viscosity were also evaluated. Three treatments were selected for producing beverages, which underwent sensory evaluation by trained tasters. Results showed red rice’s superior nutritional value compared to white rice, particularly in amino acid and mineral content. The formulated beverage, containing pre-cooked red rice and blackberry powder as a functional ingredient, was well-received for its ease of reconstitution and sensory qualities.